Women and Hereditary Bleeding Disorders - Bosch, Alessandra; Moussaoui, Dehlia; Casini, Alessandro (Hämostaseologie, 2025)
Hereditary bleeding disorders encompass a range of hemostasis defects that impair the blood coagulation process. Although these disorders affect both men and women, research and clinical management have historically been predominantly focused on male patients, particularly those with hemophilia. Consequently, the impact of these disorders on women has been undervalued and frequently overlooked. The intricate relationship between a woman's tendency to bleed and the various gynecological and obstetric processes gives rise to distinctive health challenges for women with hereditary bleeding disorders. Heavy menstrual bleeding (HMB), excessive bleeding during miscarriages, postpartum hemorrhage, and hemorrhagic ovarian cysts represent some of the most common complications. Despite the high prevalence and significant impact of these symptoms, many women experience delays in diagnosis and treatment, which in turn may result in iron-deficiency anemia, anxiety, influence on reproductive decisions, and a decreased quality of life. This review aims to summarize the distinctive characteristics of hereditary bleeding disorders in women, emphasizing the clinical challenges and hormonal management strategies for HMB.
Keywords: hemophilia carrier; von Willebrand disease; heavy menstrual bleeding; rare bleeding disorders; postpartum hemorrhage